Consensus on the descriptors, definitions, and reporting methods for heading in football studies: A Delphi study - Kerry Peek; Andrew G. Ross; Paula R. Williamson; Julia Georgieva; Thor Einar Andersen; Tim Meyer; Vincent Gouttebarge; Sara Dahlen; Mike Clarke; Andreas Serner (PLoS ONE, 2025)
Heading in football (soccer) is a complex skill involving deliberate head-to-ball contact, which may pose short-, medium-, and long-term risk to player brain health. However, understanding header exposure during matches and training sessions, as well as comparing header incidence between studies is currently challenging given the lack of standardisation in descriptors, definitions, and reporting methods. This Delphi study aimed to establish a consensus on the descriptors, definitions, and reporting methods for heading in football research to improve consistency and quality. The study involved 167 participants from diverse football-related backgrounds including coaches, players, medical personnel, and researchers, with consensus achieved to include 27 descriptors in minimum reporting criteria for heading in football research. An additional 27 descriptors were also defined for inclusion in an expanded framework. The operational definition of a header was standardised as “a head-to-ball contact where the player makes a deliberate movement to redirect the trajectory of the ball using their head.” The consensus framework provides a standardised approach to heading in football research to enhance data quality and comparability across studies. Improved header incidence data quality has the potential to contribute significantly to our understanding of the risks associated with heading in football to inform future research and practice guidelines.